2007
DOI: 10.1111/j.1750-3841.2007.00373.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Immersion Freezing in NaCl Solutions and of Frozen Storage on the Viscoelastic Behavior of Mozzarella Cheese

Abstract: The freezing of Mozzarella cheese by immersion in NaCl solutions may be an innovative procedure for the dairy industry because it combines conveniently salting and freezing processes. In this work, the influence of this type of freezing method and of the frozen storage of samples on the viscoelastic behavior of Mozzarella cheese was studied. Slabs (2 x 10 x 10 cm(3)) were immersed in 23% w/w NaCl solutions (control samples: 4 degrees C, 90 min; frozen samples: -15 degrees C, 180 min). Half of the frozen sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…This result indicates that the freezing process did not produce modifications in the extent of the linear viscoelastic region of the LFSC. Similar behaviour was observed by Ribero, Zorrilla, and Rubiolo (2007), who have studied the influence of immersion freezing in NaCl solutions and of frozen storage on the viscoelastic behaviour of mozzarella cheese. The authors published that a critical strain of 0.005 at 1 Hz was obtained from strain sweeps for both refrigerated and frozen samples, indicating that freezing process did not produce modifications in the extent of the linear viscoelastic region of Mozzarella cheese.…”
Section: Region Of Linear Viscoelasticitysupporting
confidence: 75%
“…This result indicates that the freezing process did not produce modifications in the extent of the linear viscoelastic region of the LFSC. Similar behaviour was observed by Ribero, Zorrilla, and Rubiolo (2007), who have studied the influence of immersion freezing in NaCl solutions and of frozen storage on the viscoelastic behaviour of mozzarella cheese. The authors published that a critical strain of 0.005 at 1 Hz was obtained from strain sweeps for both refrigerated and frozen samples, indicating that freezing process did not produce modifications in the extent of the linear viscoelastic region of Mozzarella cheese.…”
Section: Region Of Linear Viscoelasticitysupporting
confidence: 75%
“…In addition to the advantages associated with a fast freezing method, immersion freezing of cheeses would allow decreasing the production time because salting and freezing occur at the same time. Ribero et al (2007) shown that although the immersion freezing of Mozzarella cheese affects some of the studied viscoelastic parameters, the differences observed between frozen and frozen-stored samples with control samples were small. Microstructural studies may contribute to a better understanding of the effect of this new freezing alternative on Mozzarella cheese characteristics.…”
Section: Introductionmentioning
confidence: 47%
“…The crossover temperature can be used to identify the solid-like to liquid-like phase transitions the cheese undergoes during melting (Gunasekaran and Ak, 2003). Ribero et al (2007) observed that crossover temperature decreases as ripening time increases. Moreover, at ripening time higher than 20 days, crossover temperatures were similar for the three treatments studied.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations